Modelling and optimization of phase change materials (PCM)-based passive cooling of solar PV panels in multi climate conditions - Durez, Asif; Ali, Muzaffar; Waqas, Adeel; Nazir, Kamran; Sudhakar, Kumarasamy (Frontiers Media S.A., 2023)
To address the increasing energy demand, replacing conventional energy systems with non-conventional resources like solar power generation is crucial. Photovoltaic (PV) panels play a significant role in harnessing solar energy and converting it into electrical power. However, the solar cells’ temperature dramatically influences the panel’s performance, particularly in hot climates. In this study, a detailed mathematical model is developed and conducted simulations using three different phase change materials (PCMs)—RT21, RT35, and RT44—integrated with PV panels in various climate conditions worldwide during the summer season. An optimization model is also created using MATLAB and a genetic algorithm to identify the most suitable PCM for specific climate zones. The findings revealed that incorporating PCM resulted in a surface temperature reduction of PV panels, leading to a 6% increase in efficiency and a 16% boost in electrical output. Specifically, when using a PCM with a melting point of 21°C, the maximum cell temperature during summer operation decreased from 65°C to 38°C. Similar temperature reductions were observed when using PCMs with melting points of 35°C and 44°C. Current analysis demonstrates that the correct selection of a phase change material can decrease panel temperature by approximately 39% in June. Furthermore, PCM with a melting point of 21°C exhibited the best outcomes in terms of maximum electrical performance, efficiency, and PV cell temperature reduction.